Is Accounting Meeting the Challenge in Europe? - Kabbes, S. Madonna (The Accounting Review, 1965)
This article discusses the challenges in accounting in European countries. A survey of the literature of recent years indicates that leaders have long recognized that the profession should strive toward greater uniformity in accounting standards throughout the world. National backgrounds have had, and it appears will continue to have, a definite bearing on the development of the profession in different countries. Reporting practices, standards of training, and the status, which the profession has achieved, all reflect the effects of variations in the development of the nation's economy. The formation of the European Economic Community, formalized on March 25, 1957, when the six nations signed the Treaty of Rome, marked the beginning of a powerful economic union. Along with the many far-reaching effects on international trade and economic growth, its development is sure to have very definite effects on the accounting profession both within and beyond its borders. Training requirements for those seeking to enter the profession, as well as for continuing study for those already practicing, must take into consideration these broadening horizons.